2022
DOI: 10.3389/fpsyg.2022.752748
|View full text |Cite
|
Sign up to set email alerts
|

Moe-Phobia: Effect of Users' Gender on Perceived Sexuality and Likability Toward Manga-Like Virtual Agents

Abstract: In Japan, many incidents regarding manga-like virtual agents have happened recently, in which critics have indicated that virtual agents used in public spaces are too sexual. Prior study defined this perception as “moe-phobia.” In many cases, critics have pointed to agents' clothes. However, after verifying actual moe-phobia incidents, I hypothesize that these incidents are associated with not only the agents' clothes but also the situations in which they are used. I conducted an experiment with three factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…That is, a person does not only react simply to the external "sexual depiction" of a moe character, but the image of the character as a whole is determined by the combination of the character and the context in which it is used. Furthermore, Matsui 9 conducted a participant experiment and confirmed that moe-phobia is not influenced by only one factor, "the appearance of the character," but by two factors, "the appearance of the character" and "the context in which the character is used," showing an interaction effect. This means, in other words, that when a person views a moe character, he or she is reading two layers at the first level of "appearance characteristics" and at the second level of "social context."…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…That is, a person does not only react simply to the external "sexual depiction" of a moe character, but the image of the character as a whole is determined by the combination of the character and the context in which it is used. Furthermore, Matsui 9 conducted a participant experiment and confirmed that moe-phobia is not influenced by only one factor, "the appearance of the character," but by two factors, "the appearance of the character" and "the context in which the character is used," showing an interaction effect. This means, in other words, that when a person views a moe character, he or she is reading two layers at the first level of "appearance characteristics" and at the second level of "social context."…”
Section: Introductionmentioning
confidence: 92%
“…This corresponds to the second independent variable, "context," and is defined as the two conditions of the science museum condition and the swimming pool condition. Intuitively, "white coat" and "science museum" and "swimsuit" and "swimming pool" seem to have a high affinity with each other, and based on Matsui 9 , "swimsuit" is an appearance that gives a strong sexual impression at first glance, but when placed in the context of "swimming pool," which is an environment in which people are more comfortable seeing swimsuits, the sexual impression of and aversion toward the swimsuit are expected to be reduced. Figure 3 is images used in the experiment.…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 3 more Smart Citations